2015
DOI: 10.1002/uog.14807
|View full text |Cite
|
Sign up to set email alerts
|

Cervical condition and fetal cerebral Doppler as determinants of adverse perinatal outcome after labor induction for late‐onset small‐for‐gestational‐age fetuses

Abstract: (OR, 2.43; 95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 45 publications
1
42
1
Order By: Relevance
“…The mean or median interval between CPR measurement and delivery was < or ∼48 h in five studies, ≤ 7 days in six studies, 7–14 days in three studies, > 14 days in five studies, 1–30 days in one study and unreported in two studies. Most studies ( n = 16) used the last CPR result before delivery in analyses. Sixteen studies reported that the CPR results were not used to manage the pregnancies, one reported that they were used to manage the pregnancies and the remaining five studies did not report on this issue.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The mean or median interval between CPR measurement and delivery was < or ∼48 h in five studies, ≤ 7 days in six studies, 7–14 days in three studies, > 14 days in five studies, 1–30 days in one study and unreported in two studies. Most studies ( n = 16) used the last CPR result before delivery in analyses. Sixteen studies reported that the CPR results were not used to manage the pregnancies, one reported that they were used to manage the pregnancies and the remaining five studies did not report on this issue.…”
Section: Resultsmentioning
confidence: 98%
“…Of 1191 citations identified initially, 22 studies, including a total of 4301 women/fetuses, met the inclusion criteria (Figure ). Two studies were performed using the same cohort, one reporting results for all cases of suspected FGR and the other for cases of suspected early‐onset FGR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Prior et al showed that using a cut-off of <0.6765 MoM yielded a similar positive predictive value for caesarean section because of presumed fetal compromise as using the 10th centile. 11,13,[16][17][18] When evaluating CPR in appropriately grown fetuses, recent reports used data from healthy post-term pregnancies. 13 More recent studies agree that the sensitivity of CPR in cases with IUGR measured before 34 weeks was higher than in the overall population.…”
Section: Data Interpretationmentioning
confidence: 99%